Frontline Staff Characteristics and Capacity for Trauma-Informed Care: Implications for the Child Welfare Workforce. (December 2020) - Bosk, Emily A.; Williams-Butler, Abigail; Ruisard, Debra; MacKenzie, Michael J.
Abstract: Background: Improved understanding of the lasting ways trauma can impact self-regulatory and relational capacities have increased calls for Trauma-Informed Care (TIC) for child welfare-involved families. Little is known, however, about how the attitudes and characteristics of frontline workers impact the implementation of TIC and job retention. This work fills an important gap in knowledge regarding the relationship between staff relational capacities, the implementation of TIC and staff retention. Objective: To understand the relationship between staff characteristics, endorsement of TIC and intent to turnover. Participants and setting: Three child and family serving agencies surveyed 271 staff from a populous Northeastern state. Methods: Regression analyses were used to examine the relationship between staff characteristics, Attitudes Related to Trauma Informed Care (ARTIC) score, and intent to turnover. Results: Higher levels of staff rejection sensitivity was associated with lower endorsement of Principles of Trauma-Informed Care (p < .05). Lower staff alignment with principles of TIC was associated with higher levels of intention to turnover and leave their organization (p < .05). Conclusion: Staff histories of relational loss and trauma may impact both workforce buy-in and readiness to implement TIC. Therefore, identifying staff sensitivity to rejection in the hiring process or after hire, and providing specific supports, such as reflective supervision, may enhance both service delivery and staff experiences' of their work. Additionally, using the ARTIC scale in the hiring process may also reduce staff turnover and burnout. Attending to staff relational characteristics is a critical component of promoting worker resilience.